2007
DOI: 10.1038/sj.tpj.6500432
|View full text |Cite
|
Sign up to set email alerts
|

Association of the mu-opioid receptor gene with smoking cessation

Abstract: We investigated the association of the OPRM1 genotype with long-term smoking cessation and change in body mass index (BMI) following a smoking cessation attempt among smokers who attempted to quit using the nicotine replacement therapy (NRT) patch or placebo in a randomized controlled trial, and were followed-up over an 8-year period following their initial cessation attempt. We also investigated possible sex differences in these relationships, given evidence for sex differences in smoking cessation and centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 64 publications
(73 reference statements)
0
43
1
2
Order By: Relevance
“…Further, the current study was designed to eliminate carryover effects of smoking by scanning smokers on two separate occasions. It will be important in future studies to include sufficient numbers of males and females, as the behavioral effects of this polymorphism may be sex specific (14,18,35), and female sex and estradiol alter MOR binding availability (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the current study was designed to eliminate carryover effects of smoking by scanning smokers on two separate occasions. It will be important in future studies to include sufficient numbers of males and females, as the behavioral effects of this polymorphism may be sex specific (14,18,35), and female sex and estradiol alter MOR binding availability (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Most research on the role of genetic variation on smoking cessation pharmacotherapy has been directed to the two most widely accepted and licensed forms of smoking cessation therapy: nicotine replacement therapy (NRT) [111,[124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140] and the antidepressant bupropion (Zyban1) [129,137,[141][142][143][144][145][146][147][148][149].…”
Section: Influence Of Genetic Variations On Smoking Cessation Treatmentmentioning
confidence: 99%
“…Secondly, smokers who carry genetic polymorphisms associated with reduced nicotinic receptor (and possibly also dopaminergic) activity may experience greater benefit from nicotine spray (NS) compared with transdermal nicotine patches (TN), because of the greater rewarding effects of NS [133]. Thirdly, smokers who have increased activity variants in the m-opioid receptor (MOR) may have better success with the higher levels of nicotine delivered by TN compared with the lower levels of nicotine from NS [125,136,138], possibly only in combination with variants in MOR-interacting proteins [138]. Fourthly, an increased nicotine metabolism (determined primarily by CYP2A6 genotype but probably not by CYP2B6 genotype) lowers quit rates with TN [128,130,135].…”
Section: Influence Of Genetic Variations On Smoking Cessation Treatmentmentioning
confidence: 99%
“…34 In our previous study, we found that patients with the G allele required higher a methadone dose than those with the A allele. 35 Furthermore, rs1799971 has also been reported to be significantly associated with long-term smoking cessation in both males and females, 36 with nicotine reinforcement in women, and with the brain m-opioid receptor binding potential in smokers. 11,15 However, the results are not consistent.…”
Section: Introductionmentioning
confidence: 99%